Pengenalan Lingkungan Bersih : Program Kerja Bakti di SDN 041 untuk Generasi Peduli - Nurul Hidayat; Muhammad Aprisal; Arini Hidayah; Dina Natasa Salsabilah; Ranti Febriyani (Jurnal Pengabdian Masyarakat Nusantara, 2024)
A clean environment is an important factor in creating a comfortable and healthy learning atmosphere, especially in elementary schools where children are growing physically and mentally. The concept of introducing a clean environment from an early age has a strategic role in forming positive habits that will have an impact in the future. With the introduction of a clean environment program in elementary schools, it is hoped that students will understand the importance of maintaining a clean environment, both at school and at home prevention of stroke on the quality of life of the elderly.To provide an introduction to the concept of a clean environment in elementary schools, with the main aim of developing students' awareness and behavior in maintaining cleanliness from an early age. Implementation of Community Service Activities at State Elementary School 041 State Elementary School 041 has carried out community service activities regularly every week. This activity involves the entire school community, including the principal, teachers, students and school staff. Community service activities are carried out on Fridays every week, with a duration of around 1-2 hours. This research shows that community service activities in elementary schools are effective in introducing students to a clean environment. This activity can increase students' awareness and concern for the environment, build cooperation and a sense of shared responsibility in maintaining the cleanliness of the school environment, and become a learning tool that supports the creation of a clean and healthy environment.